From Screen to Story: Freshmen’s Writing Skills Through Multimodal Task-Based Approach - Mahmudah, Khotimah; Rakerda, Hilda; Firmansyah, Dedi Wahyu (Journal of English Language Teaching, Linguistics, and Literature Studies, 2025)
Writing remains a persistent challenge for freshmen in English as a Foreign Language (EFL) context, particularly in generating ideas, applying grammar accurately, and producing coherent texts. This study employs a case study method to investigate students’ perceptions of an e-Multimodality Workbook that integrates visual stimuli within a Task-Based Learning (TBL) framework to enhance writing proficiency in a Basic Writing class. Data were gathered from twelve purposively selected students through semi-structured interviews and analyzed using the CIPP (Context, Input, Process, Product) evaluation model. The findings show that colored visual prompts effectively enhance imagination, idea development, and comprehension of abstract concepts, whereas black-and-white images and insufficient grammatical guidance hinder clarity and engagement. A pedagogical framework was used in designing the e-Multimodality Workbook, which serves as a learning aid and a medium that facilitates assessment. A linguistic expression in term of visual meaning proses was used in this book. A technology-based adaptive learning materials that integrate multimodal tasks and student feedback is a product of this research. This supports the development of writing competencies at a higher level. Furthermore, the findings suggest that this book can enhance learner autonomy across various levels of EFL proficiency.Keyword: English Writing, Multimodality, Task-based Approach.